PREDIKSI JUMLAH PRODUKSI JAGUNG DI NUSA TENGGARA BARAT MENGGUNAKAN METODE LEAST SQUARE: Prediction of Corn Production in West Nusa Tenggara Using the Least Square Method - Ramadhan, Fitrah; Abdullah, Umar; Uluwi, Ahmad Ihsan; Robbaniyyah, Nuzla Af'idatur; Rusadi, Tri Maryono (Yayasan Al-Amin Qalbu, 2025)
Maize production is one of the main components of food in agriculture in West Nusa Tenggara (NTB) with a significant contribution to national production. However, maize production in NTB often fluctuates due to weather conditions, climate, market prices, government policies, land area, resource availability, and access to technology and information. The aims of the research is to determine the prediction of corn production in NTB for 2024-2026. This research uses the least square method to predict maize production based on historical data trends, which allows for more accurate planning. Previous studies have shown that this method is effective in producing accurate predictions for various agricultural commodities. The results are expected to provide predictions that can be used by the government and farmers for better production planning and risk mitigation, and become a reference for the development of prediction techniques in agriculture